Non-sustained ventricular tachycardia in patients with congenital heart disease: An important sign?. (1st March 2016) - Teuwen, Christophe P.; Ramdjan, Tanwier T.T.K.; Götte, Marco; Brundel, Bianca J.J.M.; Evertz, Reinder; Vriend, Joris W.J.; Molhoek, Sander G.; Reinhart Dorman, H.G.; van Opstal, Jurren M.; Konings, Thelma C.; van der Voort, Pepijn; Delacretaz, Etienne; et al.
Abstract: Background: Sustained ventricular tachycardia (susVT) and ventricular fibrillation (VF) are observed in adult patients with congenital heart disease (CHD). These dysrhythmias may be preceded by non-sustained ventricular tachycardia (NSVT). The aims of this study are to examine the 1] time course of ventricular tachyarrhythmia (VTA) in a large cohort of patients with various CHDs and 2] the development of susVT/VF after NSVT. Methods: In this retrospective study, patients with VTA on ECG, 24-hour Holter or ICD-printout or an out-of-hospital-cardiac arrest due to VF were included. In patients with an ICD, the number of shocks was studied. Results: Patients (N = 145 patients, 59% male) initially presented with NSVT (N = 103), susVT (N = 25) or VF (N = 17) at a mean age of 40 ± 14 years. Prior to VTA, 58 patients had intraventricular conduction delay, 14 an impaired ventricular dysfunction and 3 had coronary artery disease. susVT/VF rarely occurred in patients with NSVT (N = 5). Fifty-two (36%) patients received an ICD; appropriate and inappropriate shocks, mainly due to supraventricular tachycardia (SVT), occurred in respectively 15 (29%) (NSVT: N = 1, susVT: N = 9, VF: N = 5) and 12 (23%) (NSVT: N = 4, susVT: N = 5, VF: N = 3) patients. Conclusions: VTA in patients with CHD appear on average at the age of 40 years. susVT/VF rarely developed in patients with only NSVT, whereas recurrent episodes of susVT/VF frequently developed in patients initially presenting with susVT/VF. Hence, a wait-and-see treatment strategy in patients with NSVT and aggressive therapy of both episodes of VTA and SVT in patients with susVT/VF seems justified.